2001
DOI: 10.1054/bjoc.2000.1572
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-carboplatin as first line chemotherapy for epithelial ovarian cancer

Abstract: Epithelial carcinoma of the ovary is one of the most common gynaecologic malignancies, and the fourth most frequent cause of cancer death in women (Yancik, 1993). The asymptomatic early stages of ovarian cancer mean that most patients have widespread disease at the time of diagnosis. Patients with FIGO stage III and IV disease and significant residual tumour masses after primary surgery can expect a 5-year survival rate of less than 10%, despite multiple courses of platinum-based chemotherapy (Omura et al, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 29 publications
0
53
0
2
Order By: Relevance
“…These findings suggest that FAK is a substrate for docetaxel via caspase-3, and its inhibition potentiates docetaxel's apoptotic effects on ovarian cancer cells. Docetaxel is being increasingly used in clinical settings due to its greater potency compared with paclitaxel (37,38) and lower risk of neuropathy (39,40). We and others have shown that for adjuvant therapy of ovarian carcinoma, docetaxel is at least as effective as paclitaxel in combination therapy with platinum but may have a better side effect profile (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that FAK is a substrate for docetaxel via caspase-3, and its inhibition potentiates docetaxel's apoptotic effects on ovarian cancer cells. Docetaxel is being increasingly used in clinical settings due to its greater potency compared with paclitaxel (37,38) and lower risk of neuropathy (39,40). We and others have shown that for adjuvant therapy of ovarian carcinoma, docetaxel is at least as effective as paclitaxel in combination therapy with platinum but may have a better side effect profile (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…This formula is widely used in the treatment of several type of carcinoma. [23][24][25][26][27] Although it is generally considered that creatinine clearance does not accurately reflect the glomerular filtration rate, 11,12) creatinine clearance is frequently used instead because of the inconvenience of measuring the glomerular filtration rate directly. Actually, some reported an arrangement of Calvert's formula using creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…While these regimens have demonstrated impressive response rates in well-conducted phase II trials, none had been compared in a large randomized trial to the now-standard paclitaxel and carboplatin regimen. This year's ASCO presented two important studies, both containing over 1,000 patients, comparing the standard paclitaxel and carboplatin 329 Ovarian Cancer regimen to either docetaxel with carboplatin [2,3] or, alternatively, the triplet carboplatin, epirubicin, and paclitaxel [4]. The Scottish Randomized Trial in Ovarian Cancer (SCOTROC) investigators designed a trial that built on their previous phase II experience with docetaxel and carboplatin [2].…”
Section: Therapy For Newly Diagnosed and Advanced Stage Diseasementioning
confidence: 99%
“…This year's ASCO presented two important studies, both containing over 1,000 patients, comparing the standard paclitaxel and carboplatin 329 Ovarian Cancer regimen to either docetaxel with carboplatin [2,3] or, alternatively, the triplet carboplatin, epirubicin, and paclitaxel [4]. The Scottish Randomized Trial in Ovarian Cancer (SCOTROC) investigators designed a trial that built on their previous phase II experience with docetaxel and carboplatin [2]. The current phase III trial compared 3-hour paclitaxel at 175 mg/m 2 with carboplatin to docetaxel at 75 mg/m 2 over 1 hour and carboplatin.…”
Section: Therapy For Newly Diagnosed and Advanced Stage Diseasementioning
confidence: 99%